Natural Course of Activated Phosphoinositide 3-Kinase Delta Syndrome in Childhood and Adolescence - Marketa Bloomfield; Marketa Bloomfield; Adam Klocperk; Radana Zachova; Tomas Milota; Veronika Kanderova; Anna Sediva (Frontiers Media S.A., 2021)
Activated phosphoinositide 3-kinase delta syndrome (APDS), caused by mutations in PI3Kδ catalytic p110δ (PIK3CD) or regulatory p85α (PIK3R1) subunits, is a primary immunodeficiency affecting both humoral and cellular immunity, which shares some phenotypic similarities with hyper-IgM syndromes and common variable immunodeficiency (CVID). Since its first description in 2013, over 200 patients have been reported worldwide. Unsurprisingly, many of the newly diagnosed patients were recruited later in life from previously long-standing unclassified immunodeficiencies and the early course of the disease is, therefore, often less well-described. In this study, we report clinical and laboratory features of eight patients followed for APDS, with particular focus on early warning signs, longitudinal development of their symptoms, individual variations, and response to therapy. The main clinical features shared by our patients included recurrent bacterial and viral respiratory tract infections, gastrointestinal disease, non-malignant lymphoproliferation, autoimmune thyroiditis, and susceptibility to EBV. All patients tolerated vaccination with both attenuated live and subunit vaccines with no adverse effects, although some failed to mount adequate antibody response. Laboratory findings were characterized by dysgammaglobulinaemia, elevated serum IgM, block in B-cell maturation with high transitional B cells, and low naïve T cells with CD8 T-cell activation. All patients benefited from immunoglobulin replacement therapy, whereas immunosuppression with mTOR pathway inhibitors was only partially successful. Therapy with specific PI3K inhibitor leniolisib was beneficial in all patients in the clinical trial. These vignettes, summary data, and particular tell-tale signs should serve to facilitate early recognition, referral, and initiation of outcome-improving therapy.